PERGERAKAN DINDING TEROWONGAN PADA VARIASI GEOMETRI TEROWONGAN YANG TIDAK DISANGGA DENGAN ANALISA AXISYMMETRIC SKALA LABORATORIUM - Putra, Bayurohman Pangacella (ReTII, 2022)
Inward tunnel deformation can cause safety risk, such as rock squeezing and tunnel wall and roof failure. Analysis of influence of tunnel diameter and length ratio is needed to be carried out. Analysis is carried out by using Axisymmetric assuming the tunnel profile is circular and excavated in a homogen and isotrop rock mass to determine the tunnel inward total displacement. Three tunnels with different diameters, 5 m, 8 m, and 10m, are modeled separately. Total displacement is evaluated on the same D/L among these models, looking for a D/L ratio that gives no change of displacement compared to previous excavation stage. The result shows that D/L = 1/3 on the three models gives neglgible inward tunnel displacement, with 5% tolerance of approximation error. About 50% value from the maximal displacement are reached at D/L = 1. Percentage value from the maximal displacement (y) can be related to D/L by equation y = 1,49e-1,08D/L.